Experimental design and data analysis for biologists - Quinn, G. P. (Gerald Peter) 1956-; Keough, Michael J. (Cambridge University Press, 2024)
"Requiring only introductory statistics and basic mathematics, this textbook avoids jargon and provides worked examples, data sets and R code, and review exercises. Designed for advanced undergraduates and postgraduates studying biostatistics and experiment design in biology-related fields, it applies statistical concepts to biological scenarios"--Provided by publisher.